Analisis Perjanjian Jual Beli Rumah Melalui Pihak Pengembang Dengan Pembeli Yang Menggunakan Fasilitas KPR - Putri, Cherin Salsabila (Hukum dan Masyarakat Madani, 2022)
The mortgage process is easy and takes a long time. Consumers have to go through several stages and several mortgage application processes such as the requirements set by the bank, the appraisal process, calculation of bank offers, credit approval by the bank and signing of credit contracts. Problems regarding the implementation of the House Sale and Purchase Agreement through the Developer with the Buyer Using the Home Ownership Credit (KPR) facility and the inhibiting factors in the house sale agreement through the developer with the buyer using the Home Ownership Credit (KPR) facility. The research method uses a normative juridical approach. The results of the study indicate that the implementation of the House Sale and Purchase Agreement through the CV Developer. Fariz Binaku with the Buyer who uses the Home Ownership Credit Facility (KPR) at Bank Mandiri where the three parties between the developer, buyer and Bank Mandiri are interrelated and must be cooperative with each other. Developer parties and buyers must make a Deed of Sale and Purchase through PPAT by completing documents such as Identity Card, Family Card, Seller’s Tax (PPH), Buyer’s Tax (BPHTB) and along with a Power of Attorney to Charge Mortgage made between the Customer and the Bank. Inhibiting Factors in the House Sale and Purchase Agreement, especially CV consumers. Fariz Binaku who uses the Home Ownership Credit Facility (KPR) is when the loan application at the nominal application offered by the bank does not match the wishes of the consumer, the consumer is not cooperative in the transaction process, the documents are doubtful by the bank so they must be fully supported by the bank.